Betaine supplementation affects the cholesterol but not the lipid profile of pigs - Martins, José M. (2010)
This study was undertaken to investigate the effects of long termbetaine intake on the cholesterol and lipid profile of Alentejano (AL) pigs. At 36 kg body weight (BW), castrated male and female pigs fed a commercial (C) diet, were divided into two groups: i) Group C, consuming the C diet; and ii) Group CB, consuming the C diet supplemented with 1 g/kg betaine. Pigs were slaughtered at ,100 kg BW. Fasting plasma concentrations of protein, urea, glucose, TAG, phospholipids, homocysteine, total and LDL- and HDL-cholesterol were determined. Liver TAG, phospholipids, and total and free cholesterol were analyzed, as well as total lipids, cholesterol contents, and fatty acid (FA) composition of M. semimembranosus and dorsal subcutaneous fat. Betaine supplemented pigs presented significantly higher plasma concentrations of TAG, phospholipids, cholesterol, and lipoprotein cholesterol. The dorsal subcutaneous fat cholesterol concentration was also significantly higher in CB than in C pigs. No differences were detected in the most abundant FA profile (including the unsaturated to saturated FA ratio) of muscle and subcutaneous fat tissues among treatments. These data suggest that betaine induces dyslipidemia, and increases cholesterol concentration in dorsal subcutaneous fat, without affecting the FA profile of M. semimembranosus and dorsal subcutaneous fat.